Arsenic Distribution, Species, and Its Effect on Maize Growth Treated with Arsenate - Xiao-ke CI; Hua-lin LIU; Yu-bo HAO; Ji-wang ZHANG; Peng LIU; Shu-ting DONG (Journal of Integrative Agriculture, 2012)
A pot experiment was conducted to investigate the effect of different arsenic (As) levels on maize (Zea mays L.) growth and As accumulation and species in different parts of maize plants, as a guideline for production of maize in As-polluted areas with the objective of preventing As from entering the food chain, and improving understanding of the mechanisms of effect of As on plant. Zhengdan 958 was grown at five As levels added to soil (0, 12.5, 25, 50, and 100 mg kg−1 As). As concentration in maize tissues increased in the order of grain<stalk<leaf ≪root. The As concentration in maize grain exceeded the maximum permissible concentration of 0.7 mg kg−1 in China at levels of 50 and 100 mg kg−1. As species were presented in root, stalk, and grain, but organic As was the major As species identified in the grain. Maize plants were able to reduce arsenate to arsenite. Low As levels of 12.5 and 25 mg kg−1 improved maize growth and grain nutrition quality, while high levels of As 50 or 100 mg kg−1 inhibited them. Yield reduction at high As levels resulted mainly from reduced ear length, kernel number per row, and kernel weight.